Changes of polyphenols and their antioxidant activities in non-pigmented, red and black rice during in vitro digestion - Jing Yu; Xin Zheng; Dawei Zhu; Qingyu Xu; Feifei Xu; Mingxue Chen; Lingqi Meng; Yafang Shao (Food Chemistry: X)
Polyphenols, a major bioactive constituent in rice grain, require processing and digestion before being absorbed by human body. Free and bound phenolics, flavonoids and their antioxidant activities in non-pigmented, red and black rice after cooking and INFOGEST digestions of oral, gastric and intestinal phases were investigated. It showed that cooking caused great losses of polyphenols and antioxidant activity. Free ferulic, isoferulic and p-coumaric acid in most rice were highest at intestinal phase (p < 0.05). Bound ferulic acid in three colored rice, bound p-coumaric acid in black rice and catechin in red rice were higher at oral and/or gastric phase. After cooking, total flavonoids of non-pigmented and pigmented rice were highest at intestinal and gastric phase, respectively. Cyanidin-3-O-glucoside, peonidin-3-O-glucoside and quercetin peaked at intestinal phase in black rice. It suggested that black rice has a greater potential to be used in meal balance and functional product development.